Imágenes y representaciones de un espacio urbano: el papel de los medios de comunicación en la reproducción de las desigualdades - Monreal Requena, Pilar (2014)
This article has as objective to analyze the role that the media, especially the written press in your scanned paper, are in the process of stigmatization of a poor neighborhood and segregated from the Community of Madrid, Spain). To do this, we have used the news which appeared in the newspapers about one of the largest informal settlements of Spain, La Cañada Real Galiana passing through Madrid. Its near 15 km in length have identified with categories such as dirty, disorderly, chaotic, illegal and marginal, in addition with drug trafficking and other criminal activities in recent years, the creation and rapid dissemination of a narrative that stigmatized has been made possible by linking them to the opposite values to those implicit in the new model of urban development.